Flow in the Workplace: Experiencing Flow among Employees of Rehabilitation Centers - Tamar Sekhniashvili, MA; BCBA,IBA; Tamara Turashvili, Ph.D (Zien Journals, 2023)
The aim of the study was to explore the flow experience among employees of rehabilitation centers (N = 90) in Tbilisi, Georgia, with respect to variables such as subjective happiness and self-undermining behavior. Correlational analysis revealed significant relationships between the three variables, while regression analysis showed that both self-undermining behaviors and subjective happiness significantly predicted flow perception at workplace. Flow was negatively related to self-undermining, while it had positive link with subjective happiness.
Keywords: Flow; self-undermining; subjective happiness; intrinsic motivation